2015
DOI: 10.1016/j.amjsurg.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

An abdominal computed tomography may be safe in selected hypotensive trauma patients with positive Focused Assessment with Sonography in Trauma examination

Abstract: Background Positive Focused Assessment with Sonography in Trauma (FAST) and hypotension often indicates urgent surgery. An abdomen/pelvis CT (apCT) may allow less invasive management but the delay may be associated with adverse outcomes. Methods Patients in the Prospective Observational Multicenter Major Trauma Transfusion study with hypotension and a positive FAST (HF+) who underwent a CT (apCT+) were compared to those who did not. Results Of the 92 HF+ identified, 32(35%) underwent apCT during initial ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
(30 reference statements)
0
2
0
1
Order By: Relevance
“…The present study also showed that the proportions of patients undergoing initial CT gradually increased between 2004 and 2016. The usefulness of CT in emergency medical settings for trauma has been documented 23. A multicentre observational study showed that CT was associated with a reduction in emergency surgery 23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study also showed that the proportions of patients undergoing initial CT gradually increased between 2004 and 2016. The usefulness of CT in emergency medical settings for trauma has been documented 23. A multicentre observational study showed that CT was associated with a reduction in emergency surgery 23.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of CT in emergency medical settings for trauma has been documented 23. A multicentre observational study showed that CT was associated with a reduction in emergency surgery 23. CT has become more common in trauma care and is now easy to access in most emergency departments.…”
Section: Discussionmentioning
confidence: 99%
“…Focused assessment sonograph for trauma (FAST) is a medically proven method for the initial evaluation of closed intra-abdominal injuries. The portable ultrasound diagnostic system takes less time than traditional ultrasound and CT and is more mobile than CT and conventional ultrasound in terms of accuracy and sensitivity in exploring the abdominal cavity, with no significant differences [46]. It can be repeatedly and continuously examined, and the change in the amount of fluid and blood can be examined in a dynamic situation, which facilitates the examination and medical judgment of the disease [47].…”
Section: Application Of Portable Intelligent Ultrasound In the Diagno...mentioning
confidence: 99%
“…ст. и ниже, у которых была обнаружена внутрибрюшная жидкость при FAST, привело к уменьшению частоты экстренных лапаротомий с 93% до 22% и увеличению частоты ангиографических эмболизаций с 2% до 22% [14].…”
Section: тактика целенаправленной лучевой диагностикиunclassified